Determining Selection Criteria for Prospective Census and Survey Enumerators at BPS Kutai Kartanegara Regency - Rabiatul Adawiah; Aji Ratna Kusuma; Anwar Alaydrus (Administratio, 2025)
The selection of census and survey enumerators plays a crucial role in ensuring the quality of statistical data produced by Statistics Indonesia (BPS). However, at BPS Kutai Kartanegara Regency, the recruitment process for field enumerators remains administrative and lacks measurable and systematic criteria. The number of accepted enumerators is also disproportionate to actual needs. In 2024, out of 992 applicants, 784 were accepted, but only around 112 individuals (15%) were involved in field activities throughout the year. The unclear selection and assignment criteria creates an impression of subjectivity, resource inefficiency, and potential decline in public trust toward the recruitment process.This study aims to identify, analyze, and prioritize the selection criteria for census and survey enumerators to strengthen the recruitment governance. The Analytical Hierarchy Process (AHP) was employed, as it allows systematic weighting of various criteria through expert judgment and enables objective quantification of qualitative aspects. A total of 21 expert respondents were purposively selected based on their experience in recruitment and field implementation. Although limited in number, this approach emphasizes expertise validity and logical consistency (CR ≤ 0.1) over statistical representativeness. The main criteria were analyzed, namely: field experience, basic competence, digital literacy, commitment and integrity, as well as attitude and work ethics. The results show that attitude and work ethics, along with commitment and integrity, hold the highest weights of importance. This study offers an evidence-based analytical framework that can be replicated to improve recruitment governance for census and survey enumerators at the local/regional level.